2021
DOI: 10.5009/gnl20318
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Endoscopic Approach to Early Gastric Cancer in Clinical Practice

Abstract: Early gastric cancers (EGCs) are defined as gastric cancers confined to the mucosa or submucosa, regardless of regional lymph node metastasis. The proportion of EGCs has been increasing due to the increase in screening endoscopy for gastric cancers; therefore, the paradigm shift from surgical resection to endoscopic resection as a treatment modality for selected EGCs is accelerating. For successful endoscopic resection of EGCs, it is important to detect EGCs at an early stage and to accurately predict the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…M tumors are suitable for endoscopic treatment. Studies have shown that the traditional endoscopic assessment of the total invasive depth of early gastric cancer was 55.5–64.8% and 55.5–69% for M and 47–88% for SM 6,7,22,23 . Abe used the DPS system to predict the invasion depth of early gastric cancer; the results showed that the accuracy of DPS assessment was higher than that of the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…M tumors are suitable for endoscopic treatment. Studies have shown that the traditional endoscopic assessment of the total invasive depth of early gastric cancer was 55.5–64.8% and 55.5–69% for M and 47–88% for SM 6,7,22,23 . Abe used the DPS system to predict the invasion depth of early gastric cancer; the results showed that the accuracy of DPS assessment was higher than that of the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…Histological types of H. pylori -uninfected gastric cancers included signet ring cell carcinoma (12.5%) and fundic gland-type adenocarcinoma (25%). The endoscopic features of signet ring cell carcinoma include pale-colored, superficial, flat or depressed lesions located in the lower-to-middle third of the stomach.‍ ( 22 ) The endoscopic features of fundic gland type adenocarcinoma include flat elevated lesions similar to a submucosal tumor, with a whitish color, located in the middle-to-upper third of the stomach, and without atrophy in the background mucosa.‍ ( 23 ) It is necessary to consider these characteristics during endoscopic screening.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment strategy has been previously utilized for other preneoplastic and early gastrointestinal cancers, such as gastric and colonic polyps/early carcinoma and low- and high-grade dysplasia and early cancer in Barrett’s esophagus, in which endoscopic resection procedures have been a major breakthrough able to avoid more invasive surgeries, especially esophagectomy and gastrectomy. [ 31 32 33 ]…”
Section: Alternative Minimally Invasive Treatment Optionsmentioning
confidence: 99%